Basic chemistry concepts and exercises - Kenkel, John (CRC Press, 2011)
At a minimum, most chemistry-based industries require a basic knowledge of chemistry in their laboratory technicians and plant operators. This book covers the underlying essential concepts of basic chemistry, starting with atoms and molecules and including chemical nomenclature, chemical bonding, and, chemical units and calculations